A candidate tolerance gene identified in a natural population of field voles (Microtus agrestis) - Wanelik, Klara M.; Begon, Michael; Birtles, Richard J.; Bradley, Janette E.; Friberg, Ida M.; Jackson, Joseph A.; Taylor, Christopher H.; Thomason, Anna G.; Turner, Andrew K.; Paterson, Steve (Wiley, 2018)
The animal immune response has hitherto been viewed primarily in the context of resistance only. However, individuals can also employ a tolerance strategy to maintain good health in the face of ongoing infection. To shed light on the genetic and physiological basis of tolerance, we use a natural population of field voles, Microtus agrestis, to search for an association between the expression of the transcription factor Gata3, previously identified as a marker of tolerance in this system, and polymorphism in 84 immune and nonimmune genes. Our results show clear evidence for an association between Gata3 expression and polymorphism in the Fcer1a gene, with the explanatory power of this polymorphism being comparable to that of other nongenetic variables previously identified as important predictors of Gata3 expression. We also uncover the possible mechanism behind this association using an existing protein–protein interaction network for the mouse model rodent, Mus musculus, which we validate using our own expression network for M. agrestis. Our results suggest that the polymorphism in question may be working at the transcriptional level, leading to changes in the expression of the Th2-related genes, Tyrosine-protein kinase BTK and Tyrosine-protein kinase TXK, and hence potentially altering the strength of the Th2 response, of which Gata3 is a mediator. We believe our work has implications for both treatment and control of infectious disease.